2014
DOI: 10.1088/0953-8984/26/19/196001
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the development of spurious magnetism in single crystalline BaTi0.95Fe0.05O3−δwith highδby local structural probes

Abstract: BaTi₀.₉₅Fe₀.₀₅O₃-δ has been suggested to be an intrinsic dilute magnetic oxide with a clear dependence of magnetism on oxygen vacancy concentration. However, it has also been shown that the dopant Fe ions distribute themselves rather inhomogeneously within the lattice, though without disrupting the crystal phase of the parent BaTiO₃. With the help of x-ray absorption spectroscopy (XAS), here we find that the incorporation of a larger amount of anion vacancy pushes this inhomogeneity to the extreme, leading to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 55 publications
1
1
0
Order By: Relevance
“…The RIr 3 system thus form as a macroscopic coexistence of two crystalline phases, cubic C15b and cubic AuCu 3 -type with different relative percentage for different rare earths (Table I). Coexistence of similar polymorphic phases have earlier been reported in literature 11,22 . For example it is recently reported that RPt 3 B compounds form in two polymorphic crystal structures, tetragonal CePt 3 B-type and and ideal cubic perovskite-type at room temperature 11 .…”
Section: Resultssupporting
confidence: 83%
“…The RIr 3 system thus form as a macroscopic coexistence of two crystalline phases, cubic C15b and cubic AuCu 3 -type with different relative percentage for different rare earths (Table I). Coexistence of similar polymorphic phases have earlier been reported in literature 11,22 . For example it is recently reported that RPt 3 B compounds form in two polymorphic crystal structures, tetragonal CePt 3 B-type and and ideal cubic perovskite-type at room temperature 11 .…”
Section: Resultssupporting
confidence: 83%
“…The position of the edge and its shape reveal that all the Fe ions are in the 3+ state in an octahedral environment. [15][16][17] The k 2 weighted Fe K-edge EXAFS spectra (k 2 w(k)) of the sample is presented in Fig. 2(b) along with its corresponding best fit spectra, while the Fourier transform is presented in Fig.…”
Section: Resultsmentioning
confidence: 99%